2007
DOI: 10.3171/jns-07/11/1023
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal immune response in cerebral cavernous malformations

Abstract: The results of isoelectric focusing studies showed that CCM lesions had oligoclonal patterns of IgG unrelated to peripheral blood contamination, indicating selective synthesis of IgG within the lesions. This finding probably reflects a clonal expansion of B cells and/or plasmacytes in CCMs, an event that might be antigen-driven or a potential marker of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Four of these lesions were also stained for plasma cells. The immunohistochemistry technique has been described previously (52) with preliminary observations on three of these cases (53). Antibodies were chosen because of experience with them in clinical pathology applications and their successful use in formalin-fixed, paraffin-embedded tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of these lesions were also stained for plasma cells. The immunohistochemistry technique has been described previously (52) with preliminary observations on three of these cases (53). Antibodies were chosen because of experience with them in clinical pathology applications and their successful use in formalin-fixed, paraffin-embedded tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory has recently demonstrated oligoclonality of IgG in CCM lesions surgically excised from four of five patients, but not in their paired sera nor in control specimens (53).…”
Section: Preliminary Findingsmentioning
confidence: 98%
“…ultrastructural analysis, however, has suggested that the Cm phenotype might be modulated by immune responses to hemorrhage or to other lesional elements, such as these cytoskeletal proteins. 55,56 studies have demonstrated the presence of oligoclonal igG bands that are distinct from those found in peripheral lymphocytes. [55][56][57] indeed, shi et al spectra typed, cloned and sequenced specific complementary determining region 3 (CDr3) sequences of genes encod ing igG heavy variable chains.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…55,56 studies have demonstrated the presence of oligoclonal igG bands that are distinct from those found in peripheral lymphocytes. [55][56][57] indeed, shi et al spectra typed, cloned and sequenced specific complementary determining region 3 (CDr3) sequences of genes encod ing igG heavy variable chains. 57 these CDr3 sequences identify specific Bcell clonal origins and are specific for the antigen to which the igG binds.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Human CCM lesions manifest a robust oligoclonal antigen-driven immune response (Shi et al, 2007(Shi et al, , 2009). Radiation exposure can also trigger de novo development of CCM lesions (Jain et al, 2005;Nyáry et al, 2007).…”
Section: Ccm2 Haploinsufficiency Induces Rock-mediated Vascular Leakmentioning
confidence: 99%